Fostering Social-Emotional Learning during Resettlement: Learning with a Multilingual Refugee-Background Family - Fares J. Karam; Eleni Oikonomidoy (Anglica. An International Journal of English Studies)
Studies have shown how adopting social-emotional learning (SEL) approaches can help support newcomer multilingual learners of English in language classrooms. However, little is known about the role of SEL in supporting refugee-background families in out-of-school contexts. Framed within critical mindfulness and critical peace education, this study addresses this gap by asking: What role does SEL play in supporting two refugee-background parents’ resettlement and language learning efforts? and How do two refugee-background parents’ values influence weekly English tutoring sessions? The study documents different ways through which participants engage with SEL practices to negotiate their tutoring sessions and introduces “mujamalah” as an SEL practice in line with peace education. Findings underscore the importance of incorporating SEL approaches to support multilingual refugee-background families.